2010
DOI: 10.1128/jvi.00101-10
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Live-Attenuated Influenza Vaccines Based on Modifications in the Polymerase Genes Protect against Epidemic and Pandemic Flu

Abstract: Human influenza is a seasonal disease associated with significant morbidity and mortality. Influenza vaccination is the most effective means for disease prevention. We have previously shown that mutations in the PB1 and PB2 genes of the live-attenuated influenza vaccine (LAIV) from the cold-adapted (ca) influenza virus A/Ann Arbor/6/60 (H2N2) could be transferred to avian influenza viruses and produce partially attenuated viruses. We also demonstrated that avian influenza viruses carrying the PB1 and PB2 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 33 publications
4
34
0
2
Order By: Relevance
“…We chose this strain because it grows well in eggs and tissue culture and has been shown to replicate in several animal species, such as mice, chickens, and ferrets, without previous adaptation (13,21). In addition, we previously showed that LAIVs based on the wt H9N2 background have adequate attenuation and protection efficacy profiles (13,21,22).…”
Section: Generation Of Influenza Virus Vectors With Rearranged Genomementioning
confidence: 99%
“…We chose this strain because it grows well in eggs and tissue culture and has been shown to replicate in several animal species, such as mice, chickens, and ferrets, without previous adaptation (13,21). In addition, we previously showed that LAIVs based on the wt H9N2 background have adequate attenuation and protection efficacy profiles (13,21,22).…”
Section: Generation Of Influenza Virus Vectors With Rearranged Genomementioning
confidence: 99%
“…While live attenuated influenza virus (LAIV) vaccines have been approved for use in people and horses, a LAIV for swine has yet to make it to market. This is despite a number of LAIV vaccines that have been developed and demonstrated to provide significant cross-protection in experimentally infected pigs (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The WF10 virus backbone is of avian origin, whereas the Sw99 and 2009 pH1N1 virus backbones contain a triple-reassortant internal gene (TRIG) cassette with the PA and PB2 gene segments from an avian influenza virus and the PB1 gene segment from a human influenza virus. The NP, M, and NS gene segments of Sw99 are derived from a classical swine influenza virus lineage (8), while the NA and M gene segments of the pH1N1 virus are from a Eurasian swine H1N1 virus lineage and the HA, NP, and NS gene segments are from a classical swine H1N1 virus lineage (10).…”
mentioning
confidence: 99%
“…In order to develop LAIVs for use in the poultry and swine industries and to protect humans against zoonotic influenza virus infections, several groups have investigated the use of backbones comprised of gene segments from avian and/or swine viruses as an alternative to AA ca. To this end, the ts signature from the AA ca virus has been experimentally inserted into a backbone of influenza A/Guinea fowl/Hong Kong/WF10/99 H9N2 virus (WF10) (6,7), A/swine/Wisconsin/14094/99 H3N2 virus (Sw99) (8), and 2009 pandemic HIN1 (pH1N1) influenza A/New York/1682/2009 virus (NY1682) (9). The WF10 virus backbone is of avian origin, whereas the Sw99 and 2009 pH1N1 virus backbones contain a triple-reassortant internal gene (TRIG) cassette with the PA and PB2 gene segments from an avian influenza virus and the PB1 gene segment from a human influenza virus.…”
mentioning
confidence: 99%